Product Quality, Price Perception, Customer Loyalty on IM3-Indosat SIM Card's Users - Ardiansyah, Tri Endi; Dara, Nursimah; Nasution, Doni Alnis (MultiTech Publisher, 2024)
This study aims to examine the impact of Product Quality and Price Perception on Customer Loyalty. The research is quantitative and employs a survey methodology. The sample consists of 100 respondents. Primary data was analysed using SPSS version 26 for evaluation. The analysis results indicate that both Product Quality and Price Perception have a positive and significant influence on Customer Loyalty, with a significance value of 0.000 less than 0.05 and F-count of 146.348 greater that F-table 3.09. The coefficient value shows that 75.1% of Customer Loyalty is explained by Product Quality and Price Perception. These findings confirm the initial hypothesis, demonstrating a positive and significant effect of Product Quality and Price Perception on Customer Loyalty at 75.1%.